Microbiome dynamics associated with the infection of grey field slugs by the biocontrol nematode Phasmarhabditis hermaphrodita - Ha, Anh D.; Howe, Dana K.; Colton, Andrew J.; Mc Donnell, Rory J.; Denver, Dee R. (Frontiers in Microbiology, 2025)
The facultative-parasitic nematode Phasmarhabditis hermaphrodita has been used for many years as a biological control agent targeting slug pests. During the nematode’s infection process, the presence of certain bacteria has been suggested to affect the pathogenicity and efficiency of the nematodes in killing slugs, though the potential roles of different bacteria in affecting host-infection by nematodes remain unclear. In this study, we examined three experimental P. hermaphrodita populations cultured with three different bacteria: 1) Escherichia coli (EC), 2) a newly isolated Pseudomonas sp. strain (PS) that co-cultured with a P. hermaphrodita strain found in Oregon, USA, and 3) the original complex bacterial community (BC) associated with the nematode. For each treatment, we evaluated the pathogenicity of P. hermaphrodita at low and high concentrations towards adult grey field slug Deroceras reticulatum and investigated changes in the nematode microbiome structure before and after slug infection. Slugs exposed to EC, of both low and high concentration treatments, survived significantly longer than slugs exposed to PS high and BC high. Slugs in the BC low treatment survived significantly longer compared to BC high, but significantly shorter compared to EC high. We identified a wide variety of taxa components (82 genera) in the community associated with the nematode pre-infection, most of which were of low abundance. In all bacterial treatments post-infection, the number of genera almost quadrupled and the abundance of these taxa changed remarkably, although the taxa with the highest abundance remained stable. We also observed four Pseudomonas amplicon sequence variants (ASVs) that increased in abundance after slug infection in the Pseudomonas treatment. This finding suggests these taxa may play a role in the infection process, potentially acting as opportunistic pathogens, or facilitating infection progression through providing nematodes with a favorable food source, or contributing directly to the nematode’s virulence.